Polymerase Chain Reaction-Restriction Fragmet Lenght Polymorphism (PCR-RFLP) Analysis of Mitochondrial Cytochrome C Oxidase 1 (CO!) Gene in Angelwing Clam (Pholas orientalis) in Western Visayas, Philippines - Ponte, Kirstie Angelii P. (2015.)
The angelwing clam (Pholas orientalis) or ?diwal? is an important economic commodity that faces endangerment in the coastal waters of Western Visayas because of anthropogenic and natural disturbances. A molecular diagnostic marker of P. orientalis from four sampling sites in Western Visayas was developed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) Analysis, which involved PCR amplification of the mitochondrial cytochrome oxidase (COI) gene followed by digestion using restriction enzymes (AccI, BstDE I and AccI + BstDE I). In silico RFLP analysis was conducted as comparative basis of restriction patterns for in vivo RFLP analysis of GenBank COI sequences in China (KJI25423, KJI25422 and JQ267793) and samples in Western Visayas. Double digest of AccI and BstDeI, which produced four gene fragments, served as the genetic marker specifically for samples in Western Visayas to distinguish them from GenBank COI sequences in China. Despite the genetic variability (Seq_1,2,3) of samples in Western Visayas, the restrictions patterns generated within populations of P. orientalis in Western Visayas showed no geographic differentiation. PCR-RFLP analysis of COI, combined with in silico restriction analysis of sequences, can serve as an important rapid identification and validation technique for population studies of P. orientalis. The molecular marker can establish future genetic-based stock enhancement and breeding strategy of the angelwings.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo
Keywords: Angelwing Clam, Pholas orientalis; Angelwing Clam, Pholas orientalis -- Western Visayas